AgDataHub Migration and Capacity Building at Mali Meteo, Bamako, Mali - Sidjesse, M.; Toure, H.; Diallo, A.; Dhulipala, R. (2025)
This report presents the outcomes of a capacity-building mission focused on the migration and enhancement of the AgDataHub Mali platform to support climate information services for improved agricultural decision-making. A total of 15 participants from ILRI, AfricaRice, Mali Meteo, and UMITI Technologies contributed to the migration of the Ag data hub to the server of Mali-Meteo and the capacity building of the staff in the operationalization. Over three days, the team conducted a needs assessment, initiated platform migration to a public-facing server (https://agdata.malimeteo.ml/), and addressed key challenges including firewall restrictions, incomplete datasets, absence of Mali Meteo generated weather data, and the need for platform localization. Collaborative discussions with Mali-Meteo staff resulted in a prioritized roadmap focused on improving data integration, user interface functionality, and long-term system ownership. This activity concluded with a shared commitment to enhancing the platform sustainability and relevance to end users. The successful advancement of the AgDataHub platform is expected to strengthen Mali climate resilience by providing accessible, accurate, and user-driven climate and agricultural information services.